Alpha-synuclein abundance and localization are regulated by the RNA-binding protein PUMILIO1 - Maximilian Cabaj; Pietro G. Mazzara; Zachary A. Gaertner; Ruizhi Wang; Michaela M. Pauers; Lisa K. Randolph; Cláudio Gouveia Roque; Sean Feeney; Serena Raimo; Nicola de Prisco; Alexei Chemiakine; Xinyuan Wang; et al. (Cell Reports)
Summary: The protein α-synuclein, encoded by SNCA, accumulates in Parkinson’s disease (PD) and other synucleinopathies for reasons that remain unclear. Here, we investigated whether SNCA is regulated in vivo by the RNA-binding protein PUM1. We establish that PUM1 binds to SNCA’s 3′ UTR in mouse and human cells. In induced neurons from patients with SNCA locus triplication, PUM1 mRNA levels are lower than in healthy controls, but increasing PUM1 normalizes both SNCA mRNA and α-synuclein protein levels, largely by suppressing the long 3′ UTR SNCA isoform. In microfluidic chamber experiments, silencing PUM1 causes a redistribution of SNCA between the soma and axons. We also show that the previously described miR-7 regulation of SNCA mRNA requires PUM1. Lastly, we report finding several individuals with PD in clinical databases bearing variants in PUM1 that affect its RNA-binding ability. Understanding how RNA-binding proteins regulate α-synuclein could lead to viable new therapies for synucleinopathies.